New Frontiers on ER Stress Modulation: Are TRP Channels the Leading Actors? - Vestuto, Vincenzo; Di Sarno, Veronica; Musella, Simona; Di Dona, Giorgio; Moltedo, Ornella; Gomez-Monterrey, Isabel Maria; Bertamino, Alessia; Ostacolo, Carmine; Campiglia, Pietro; Ciaglia, Tania (International journal of molecular sciences, 2022)
The endoplasmic reticulum (ER) is a dynamic structure, playing multiple roles including calcium storage, protein synthesis and lipid metabolism. During cellular stress, variations in ER homeostasis and its functioning occur. This condition is referred as ER stress and generates a cascade of signaling events termed unfolded protein response (UPR), activated as adaptative response to mitigate the ER stress condition. In this regard, calcium levels play a pivotal role in ER homeostasis and therefore in cell fate regulation since calcium signaling is implicated in a plethora of physiological processes, but also in disease conditions such as neurodegeneration, cancer and metabolic disorders. A large body of emerging evidence highlighted the functional role of TRP channels and their ability to promote cell survival or death depending on endoplasmic reticulum stress resolution, making them an attractive target. Thus, in this review we focused on the TRP channels’ correlation to UPR-mediated ER stress in disease pathogenesis, providing an overview of their implication in the activation of this cellular response.